2018
DOI: 10.1177/0271678x18810615
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperglycemia on neurovascular coupling and cerebrovascular patterning in zebrafish

Abstract: Neurovascular coupling (through which local cerebral blood flow changes in response to neural activation are mediated) is impaired in many diseases including diabetes. Current preclinical rodent models of neurovascular coupling rely on invasive surgery and instrumentation, but transgenic zebrafish coupled with advances in imaging techniques allow non-invasive quantification of cerebrovascular anatomy, neural activation, and cerebral vessel haemodynamics. We therefore established a novel non-invasive, non-anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 63 publications
(76 reference statements)
5
37
0
Order By: Relevance
“…Glucose exposure impaired both vascular NO production and vascular mural cell number, which builds on our previous work showing that tectal endothelial patterning is impaired by glucose exposure (Chhabria et al, 2018). These effects were also associated with reduced endothelial klf2a expression, which is known to promote vascular inflammatory gene expression, thrombosis, and atherosclerosis (SenBanerjee et al, 2004a;Lin et al, 2005).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Glucose exposure impaired both vascular NO production and vascular mural cell number, which builds on our previous work showing that tectal endothelial patterning is impaired by glucose exposure (Chhabria et al, 2018). These effects were also associated with reduced endothelial klf2a expression, which is known to promote vascular inflammatory gene expression, thrombosis, and atherosclerosis (SenBanerjee et al, 2004a;Lin et al, 2005).…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have linked hyperglycemia and pharmacologically induced diabetes to reductions in cerebral blood flow (Dandona et al, 1978;Stevens et al, 2000). A recent study demonstrated rescuing effects of the NO donor, SNP, on hyperglycemia induced neurovascular uncoupling (Chhabria et al, 2018). Using the same protocol as described in (Chhabria et al, 2018) to induce hyperglycemia in larval zebrafish, we have now described multiple effects of hyperglycemia on cellular markers of the NVU, essential for regulation of CBF and on zebrafish behaviour.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations